Sjögren syndrome induced by anti PDL-1 treatment for TNBC: case report and review of literature - Pellegrino, Caterina; D’Antonio, Chiara; Ierinò, Debora; Onesti, Concetta Elisa; Aschelter, Anna Maria; Santini, Daniele; Mazzuca, Federica (Frontiers in Immunology, 2024)
Background Rheumatological toxicity associated with immunotherapy, particularly Sjögren’s syndrome (SjS), has been observed with variable incidence in patients treated with immune checkpoint inhibitors (ICIs). Although SjS is a well-known autoimmune disease, its occurrence as an immune-related adverse event (irAE) during cancer treatment is less well understood. Current literature documents a range of incidence rates and clinical manifestations of SjS in patients undergoing ICI therapy, highlighting the need for early diagnosis and multidisciplinary management. Case presentation A 40-year-old woman underwent mammography, which revealed a 43 mm mass in the left breast. Core biopsy confirmed grade 3 infiltrating triple negative ductal carcinoma with high MIB-1. She received neoadjuvant chemotherapy, followed by surgery and radiotherapy. A CT scan in September 2022 showed lung nodules and lymph node involvement. A lung biopsy confirmed breast cancer metastasis. She started treatment with atezolizumab and nab-paclitaxel with evidence of a partial response. Nab-paclitaxel was discontinued due to side effects and atezolizumab was continued as maintenance therapy. After four cycles, the patient developed symptoms consistent with Sjögren’s syndrome (SjS), which were confirmed by diagnostic tests. Treatment with prednisone, pilocarpine and hydroxychloroquine was initiated alongside ongoing immunotherapy. The patient continues to receive atezolizumab with stable disease and good quality of life. Conclusion This case highlights the importance of recognizing SjS as a potential irAE in patients treated with ICIs, particularly those with TNBC. Multidisciplinary collaboration is essential for the prompt diagnosis and effective management of SjS to maintain both cancer control and patient quality of life. Given the recent emergence of these events and the lack of specific guidelines, our case report may provide valuable insights into the management of a little-known adverse event and pave the way for further real-world data collection on the management of these rare but significant toxicities that impact on patient quality of life. Further research is needed to optimize treatment protocols and outcomes for patients experiencing rheumatological irAEs during cancer immunotherapy.